The Influence of Green Marketing on Purchasing Decisions Mediated by Purchase Intention - Zahara, Rita (Greenation International Journal of Economics and Accounting, 2024)
This study aims to determine: (1) The direct effect of green marketing on purchasing decisions for The Body Shop customers at Paskal Hyper Square Bandung (2) The effect of green marketing on buying interest in The Body Shop customers at Paskal Hyper Square Bandung (3) The effect of buying interest on purchasing decisions for The Body Shop customers at Paskal Hyper Square Bandung (4) The effect of green marketing on purchasing decisions mediated by buying interest in The Body Shop customers at Paskal Hyper Square Bandung. This research design is survey research. The population in this study were all customers who knew The Body Shop products. The sampling technique used purposive sampling method with a sample size of 180 people. Data collection techniques using questionnaires that have been tested for validity and reliability. The data analysis technique used to answer the hypothesis of this study is the path analysis test. The results of this study indicate that: (1) there is a positive and significant direct effect of green marketing on purchasing decisions on The Body Shop customers at Paskal Hyper Square Bandung, as evidenced by the significance value of 0.000 <0.05 and the regression coefficient has a positive value of 0.686; (2) there is a positive and significant effect of green marketing on buying interest in The Body Shop customers at Paskal Hyper Square Bandung, as evidenced by the significance value of 0.000 <0.05 and the regression coefficient has a positive value of 0.561; (3) there is a positive and significant effect of buying interest on purchasing decisions for The Body Shop customers at Paskal Hyper Square Bandung, as evidenced by the significance value of 0.000 <0.05 and the regression coefficient has a positive value of 0.567; and (4) there is a positive and significant effect of green marketing on purchasing decisions mediated by buying interest in The Body Shop customers at Paskal Hyper Square Bandung, as evidenced by the mediation coefficient of 0.2087 with a significance value of 0.000 less than 0.05.